Sistem Aplikasi Manajemen Sekolah Menggunakan Metode Kualitatif dengan Pengembangan Sistem Watterfal - Rosyid, Dimas Abdul; Surojudin, Nurhadi; Ardiatma, Dodit (Forum Kerjasama Pendidikan Tinggi (FKPT), 2024)
School management is very necessary in educational institutions, because school management can help in managing work at school. However, quite a few schools do not have a school management system, due to a lack of facilities and budget for school operations. Mi Ma'arif NU Salafiyah is one that requires a school management system. Data management is not well organized, and there is no school bell as a sign of time, so that there are often delays in entering class, taking a break and returning home from school when teaching and learning activities (KBM) take place. In this research the author used quantitative methods and produced a school management application system. In school management, this includes management systems such as automatic bells, manual bells, teacher absences, recording late students, teacher data, student data, subject data, class data, and web-based teacher teaching scheduling in classes. In the design, modeling or design will be used using Unified Modeling Language (UML). This management application system will later use the Waterfall method as a system development method, using programming languages such as PHP, CSS, Javascript, supported by MySQL as a database system, using the Bootstrap framework as front-end development on the website, and DomPDF is used as one of the libraries PHP to create PDF. The results of this research refer to a web-based school management system which was then implemented, then became a school management application at the Mi Ma'arif NU Salafiyah school, so that later school management could be smarter, more effective and efficient, as well as better in data processing, and can reduce errors due to human error.